ON THE LATE WINTER AND EARLY SPRING MIGRATION OF THE INDIAN SHAD, HILSA ILISHA (HAMILTON), IN THE GANGETIC DELTA - Jones, S (Indian Journal of Fisheries, 2015)
The migration of the Indian Shad, Hilsa ilisha (Hamilton), up the major river systems when they are in floods is well known. Some time ago, while making observations on the biology and fishery of Hilsa in Bengal and Orissa, a regular small-scale movement of the fish was noticed from the lower reaches of estuaries soon after the peak of winter season, even in the absence of floods (Jones, 1952). The observations were summarised by the author in the following lines (Jones, 1952, p. 66).